Relationship Between Working Length of Pharmacy Personnel, Working Length of Doctors and Treatment Length of Patients with the Availability of Medicine in the Era of National Health Insurance (JKN) in the Hospital Grandmed Lubuk Pakam in 2024 - Pasaribu, Anita; Br Bangun, Sri Melda; Kusuma, Teja (Jurnal FARMASIMED (JFM), 2024)
Background: Quality public health services must have sufficient quantities and varieties of medicines when needed. The availability of these medicines can be ensured through good pharmaceutical standards and regulations. Optimal availability of medicines is the availability of medicines that can meet patient needs. One important step in medication management is the purchase of medicines. If the purchase of medicines is not managed carefully and responsibly, for example buying more medicines than needed, it will result in wasteful budget, increased purchasing and storage costs, and medicines or goods cannot be distributed. or expired.Objectives: To find out what factors influence the availability of drugs in the health insurance era (JKN) at the Grandmed Lubuk Pakam Hospital in 2024.Research method: This type of research is quantitative and is descriptive quantitative with a cross-sectional time approach. Results: There is a relationship between the length of service of pharmacists. The length of service of doctors and the length of treatment of patients with the availability of drugs in the era of JKN at the Grandmed Hospital in Lubuk Pakam in 2024. Conclusion: The availability of medicine for the community is one of the government's commitments in implementing public health services. The efforts made by the government are certainly aimed at maintaining public health.